Influence of windproof layer on heat and mass transfer in porous textiles based on experiment and simulation. (March 2023) - Shen, Hua; Teng, Feng; Bai, Ting; Zhang, Guangrui; Chen, Yu; Wen, Run; Xu, Guangbiao; Wang, Meng; Wang, Fumei; Wang, Jilong; Tu, Lexi
Abstract: A three-dimensional model was developed based on the experimental test setup to investigate heat and mass transfer in a porous textile under various windy conditions. Coupled conduction, natural and forced convection were modelled by CFD approach. Good agreement of simulated heat flux and thermal conductivity was observed between the experiment and simulation. The velocity and temperature distribution obtained from the model suggested that external cold air can freely enter into the porous structure of textile due to its high porosity and significantly accelerate the interior air movement (ambient wind velocity: 0.1 m/s - 3.0 m/s). Consequently, the thermal insulation of textile was aggravated since the heat transmitting through interior air obviously increased by 210.6% under stronger windy conditions. Differently, the thermal insulation was constant under various windy conditions when the porous textile was covered with a windproof layer. Besides, the heat transfer contributed from fiber and air nearly unchanged with higher wind velocity, demonstrating negligible influence exerted from ambient wind on inner air movement with the help of windproof layer. Comprehensive parametric work was also carried out to illustrate the effects of porosity, ambient temperature and permeability on the heat dissipation and interior airflow movement. Highlights: Influence of windproof layer on fluid motion and heat transfer in porous textiles was explored using CFD method. Coupled conduction, natural and forced convection were simultaneously modelled. Air movement and temperature distribution in textiles were investigated. Effect of porosity, ambient temperature and permeability on heat dissipation and interior air flow movement was clarified.